The Routledge Handbook of Religion and the Body - Greenberg, Yudit Kornberg (Routledge Handbooks in Religion Ser., 2023)
Cover -- Half Title -- Series -- Title -- Copyright -- Contents -- List of Contributors -- Introduction -- Part I Theology and Embodied Religiosity -- 1 Subtle Bodies and Ecology: Intersubjectivity, Alterity, and New Materialism -- 2 Affect and Embodied Emotions -- 3 Embodiments of Love in Jewish Sources -- 4 Apophatic Theophanies: Incarnational Knowledge of God in Early Eastern Christianity -- 5 Disability and Embodied Theology -- 6 "We Shall Do and We Shall Understand": Embodied Theology in Modern Judaism -- 7 Transfiguration -- 8 The Ruse of Body Language among Muslim Traditionists -- 9 Avoidance, Aversion, and Intellectualization: Embodied Brokenness in White Christianity -- 10 Ecological Theology and the Body -- Part II Gender, Sexuality, and Body Regulations -- 11 Bodies of Becoming: The Regulation of Religion and Gender and the Subjectivation of the Secular Body -- 12 Maternal Bodies and Religions -- 13 Semen and the Self in a Teaching and Prayer -- 14 "I Too Desired a Child": Sufi Hagiography, Ibn Khafif, and the Problem of Celibacy -- 15 Corporeal Conscientization: Heralding the Good News of Black Women's Bodies -- 16 Islamic Shi'i Ethics and the Biopolitics of the Maternal Body -- Part III Ritual and Performance -- 17 Tantric Bodies, AI Immortality, and a Yogurt Model of Self -- 18 Holy Heads: ReMembering John the Baptist and Husayn in Early Christian and Islamic Pilgrimage -- 19 Mothers in the Temple: Motherhood, Filial Piety, and Salvation Rituals in Premodern Japanese Buddhism -- 20 Body, Community, Cosmos: A Śaiva Siddhānta Rite of Initiation -- 21 (In)Conspicuous Consumption: Food, the Child Body, and Inversion of HardCore Rituals in Hindu Tantras -- 22 The Buddhist Body in a Pill: Notes Towards a Material History of Tantra in Tibet -- 23 Performing Kṛṣṇa's Body in Kerala -- 24 Sikh Langar: Tasting the Transcendent.